1977
DOI: 10.1128/aac.11.5.852
|View full text |Cite
|
Sign up to set email alerts
|

Clavulanic Acid: a Beta-Lactamase-Inhibiting Beta-Lactam from Streptomyces clavuligerus

Abstract: A novel ,8-lactamase inhibitor has been isolated from Streptomyces clavuligerus ATCC 27064 and given the name clavulanic acid. Conditions for the cultivation of the organism and detection and isolation of clavulanic acid are described. This compound resembles the nucleus of a penicillin but differs in having no acylamino side chain, having oxygen instead of sulfur, and containing a (3-hydroxyethylidine substituent in the oxazolidine ring. Clavulanic acid is a potent inhibitor of many 8-lactamases, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
320
1
8

Year Published

1978
1978
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 647 publications
(334 citation statements)
references
References 14 publications
5
320
1
8
Order By: Relevance
“…The first β‐lactamase inhibitor to be used was clavulanic acid ( 51 , discovered at Beecham Pharmaceuticals) in the mid‐1970s,166 followed over the next decade by sulbactam ( 52 )167 and tazobactam ( 53 ) 168. As seen in Figure 35, these β‐lactamase inhibitors all possess a β‐lactam core, but they have been shown to have only limited antibiotic activity.…”
Section: β‐Lactamase Inhibitorsmentioning
confidence: 99%
“…The first β‐lactamase inhibitor to be used was clavulanic acid ( 51 , discovered at Beecham Pharmaceuticals) in the mid‐1970s,166 followed over the next decade by sulbactam ( 52 )167 and tazobactam ( 53 ) 168. As seen in Figure 35, these β‐lactamase inhibitors all possess a β‐lactam core, but they have been shown to have only limited antibiotic activity.…”
Section: β‐Lactamase Inhibitorsmentioning
confidence: 99%
“…There is great interest in antibiotics that are resistant to fl-lactamase hydrolysis and in compounds that are inhibitors of 8B-lactamases (2,5,11 (11). Recently, naturally occurring inhibitors of ,B-lactamases produced by streptomyces have been discovered (1,14). Cefoxitin and cefuroxime, two new fi-lactam compounds, have been reported to be resistant to B8-lactamases of gram-negative bacilli (3,12).…”
mentioning
confidence: 99%
“…The isolates were primarily tested for their ability of β-lactamase inhibitor by the specific synergistic bioassay [20] using a resistant test strain of E. coli. CA was detected by thin-layer chromatography (TLC) [21]. It was determined by spectrophotometric method at 312 nm after derivatization with imidazole according to Bird et al [22], and confirmed the structure of the CA by high performance liquid chromatography (HPLC) assay [23].…”
Section: Streptomyces Isolation and Cultivation Conditionsmentioning
confidence: 99%